Minority languages in Europe: Problems of Albanian as the second official language in North Macedonia - Manjola Zaçellari; Flamur Shala (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study aimed at analyzing the status of Albanian as the second official language in North Macedonia, by firstly giving an overview of the language policy in the European Union (EU), its approach to multilingualism, stressing out the idea that a similar multilingual policy can be used as a model by other European countries. The study analysed the current situation regarding the use and application of the Albanian language in North Macedonia, by analyzing the law on languages and some issues regarding Albanian as the language of instruction. Qualitative methods were used for the aims of this study. The data was collected through document analysis for analyzing how the EU deals with multilingual issues; identify arising issues due to the use of Albanian as the second official language in North Macedonia and through semi-structured interviews with Albanian teachers from various schools to investigate their perceptions of the status of Albanian and about problems they face in their work routine. Teachers were posed five interview questions. After evaluating the data, some important issues were identified such as the need for further improvement to the law on languages, the need for opening more Albanian schools, and the need for continuous training for teachers.